“Existential Catastrophe Anxiety”: Phenomenology of Fearful Emotions in a Subset of Service Users With Severe Mental Health Conditions - Heggdal, Didrik; Borgejordet, Synne; Fosse, Roar (Frontiers in Psychology, 2022)
A subset of people with severe mental health conditions feel they are on the verge of losing control, even in the absence of external threats or triggers. Some go to extreme ends to avoid affective arousal and associated expectations of a possible, impending catastrophe. We have learned about such phenomenological, emotional challenges in a group of individuals with severe, composite mental health problems and psychosocial disabilities, and with long treatment histories in the mental health care system. These individuals have been encountered at a specialized inpatient ward offering exposure-based therapy that aims at restoring self-regulation and recovery. We describe the phenomenology of anxiety and fear presented by these service users, a fear we have called existential catastrophe anxiety (ECa). We also suggest a set of underlying, interacting, psychological mechanisms that may give rise to ECa. We compare ECa with three other constructs previously described in the literature - annihilation anxiety, ontological insecurity, and affect phobia. These comparisons show several similarities, but also unique qualities with ECa and its suggested underlying mechanisms. The conceptualization of ECa may aid clinicians in addressing extreme experiential turmoil and engage the service users in empowering therapeutic projects.